Pelatihan dan Pengembangan Branded Produk UMKM Desa Bedono Kluwung Kabupaten Purworejo - Jatmoko, Dwi; Purwanto, Joko; Nur Rohman, Fikri; Isti Arfiana, Shinta (Jurnal Pengabdian Pada Masyarakat Indonesia, 2023)
The role of students for society is needed. Students are agents of change for society in a better direction. Community Service Program (KKN) is a form of community service as a form of research in the field of science and technology to improve human resources in society. Group 27 Thematic Real Work Lecture (KKNT) Muhammadiyah University Purworejo for the 2022/2023 academic year was held in Bedono Kluwung Village, Kemiri District, Purworejo Regency. The KKNT activities were carried out from 5 January 2023 – 2 February 2023. Prior to the implementation of the KKNT, observations were made to determine the condition of the location. Observations were carried out using the following methods: (1) question and answer, (2) documentation, and (3) looking directly at the field. Knowing the potential and conditions in Bedono Kluwung Village, UMP KKN students organize work programs that can help and support the progress of Bedono Kluwung Village. The work programs are the Juvenile Delinquency Education Seminar at SMA Negeri 4 Purworejo, Public Health, namely Parenting, and UMKM in the village of Bedono Kluwung. In carrying out these programs, of course, we really need help from the people of Bedono Kluwung village. After we made observations, it turned out that many people already had small home-based businesses. Among them there is making salted eggs, making rengginang from cassava, making herbal medicine from spices, making birthday cakes and puddings and many others. In accordance with the theme of this year's KKNT "Economic Improvement Through Technology Transformation" our group wants to help introduce these products through social media in an even more interesting way, because on average they sell their products in traditional markets, even though there are one or two who have used this method. The form of the work program from our group is making interesting pamphlets for MSME actors in the village of Bedono Kluwung, Kemiri, Purworejo. Because through pamphlets, we are sure that their business and products will be better known by the wider community if they are disseminated, especially through social media. With the work program implemented, it is hoped that it can provide benefits and knowledge and thoughts for the people of Bedono Kluwung Village.